STRATEGI PENGEMBANGAN PEMASARAN INDUSTRI RUMAH TANGGA RAFLESIA DI DESA SUMBER AGUNG KECAMATAN ARMA JAYA KABUPATEN BENGKULU UTARA - Lestari, Dwi; Sukiyono, Ketut; Badrudin, Redy (Jurnal AGRISEP, 2015)
The purpose of this research are (1) to determine the priority of the product should be developed and used as priority by Raflesia’s home industry and (2) to determine the priority of marketing strategy appropriate and effective in the development of marketing home industry Raflesia for main products. The alternative have been used in selected the main products home industry Raflesia are Nila Crispy, Instan Jahe and Terong Crispy. Meanwhile the alternative have been used in selected development marketing strategy for the main products home industry Raflesia are 4P (product, price, distribution and promotion). To find the priority main products and marketing development strategy for the main product home industry Raflesia used Analytical Hierarchy Process (AHP) method. Based on the research, showed that the priority alternative products in a selected the main products home industry Raflesia are Instan Jahe, Nila Crispy and Terong Crispy with the weight 0.43, 0.35, 0.22 respectively. Furthermore, the priority alternative strategy in the selected of marketing development strategy for instant Jahe product of home industry Raflesia are strategy of promotion, product, distribution and price with the weight 0.32, 0.28, 0.23, 0.17 respectively.